Does habitat heterogeneity affect the diversity of epigaeic arthropods in vineyards?. (22nd November 2017) - Gonçalves, Fátima; Carlos, Cristina; Aranha, José; Torres, Laura
Abstract: The aims of this research performed in vineyards within the Douro Demarcated Region were to determine the species composition of vineyard epigaeic arthropods assemblages and to determine the influence of certain factors on their activity densities and diversity: (i) landscape composition in buffers (125, 250, 500 and 750 m) around each study site; (ii) adjacent vegetation; and (iii) vineyards' ground cover. Arthropods' were assessed using pitfall traps located inside the vineyards at three distances from adjacent vegetation (5, 50 and 100 m). Activity densities and diversity increased from spring to summer for all the studied trophic groups (omnivores, detritivores, predators, phytophages), thus showing them to be affected by season. The activity densities of phytophages were always higher at a distance of 5 m from the adjacent vegetation, which suggests that, although they could originate from these habitats, they do not move too far into the vineyard. Predators reported higher activity densities at 5 m during spring. Meanwhile, in summer, no significant differences were found with the increasing distance from the edge. This result suggests that these habitats could serve both as a refuge and a hibernation habitat, from which predators could colonize the vineyard.